Equilibrium and Kinetic Studies of Adsorption of Safranin-O from Aqueous Solutions using Pineapple Peels - Mohammed, M. A.; Ibn Abubakar, B. S. U.; Kurna, B. B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2017)
The aim of this work is to investigate the applicability of raw unmodified pineapple peel waste (PPW) for the removal of safranin-O in aqueous solution. The adsorption of safranin on PPW material was studied as a function of PPW dose (0.5–2.5g), initial concentration (20–100mg/L), pH, 2–10solutions, and a varying contact time. The effect of these parameters on the adsorption capacity was studied using a batch process. The experimental data were fitted to Langmuir and Freundlich adsorption models. The adsorption isotherm was found to obey the Freundlich model. The adsorption capacity was found to be 21.7mg/g. Kinetic data were fitted to the pseudo-first-order and pseudo-second-order models, and were found to follow pseudo- second-order kinetic model. The result shows that PPW adsorbent is potentially low-cost adsorbent for removal of safranin-O.